Upaya Peningkatan Pemahaman Materi Mata Kuliah Matematika Dengan Menerapkan Pilar-Pilar CTL (Contextual Teaching And Learning) Pada Mahasiswa S1 PGSD Pokjar Kota Madiun. (Kajian Konseptual) - Tresnaningsih, Sri (JURNAL AGRI-TEK, 2015)
Students Elemantery Education Universitas Terbuka (UT) in Madiun includes students PGSD and PGPAUD. For S-1 PGSD is input D-2 PGSD and high school backgrounds of various inputs such as from high school science, high school social studies, vocational school with a variety of majors. Clumps mathematics courses listed in the curriculum of UT are in the 2nd half, 3.4 and 8. Mathematics with code PDGK 4108 consists of 12 modules contains more high school math material. Being material to SD's more widely discussed in the module Mathematics Education I, II modules Mathematics Education and Learning Mathematics in Elementary School. Research on "Efforts to improve the understanding of the subject matter of mathematics by applying pillars CTL (Contextual Teaching and Learning) Students S-1 PGSD Madiun" against the background of the fact on the ground that the learning process in the tutorial that lasts for 8 sessions @ 120 minutes. The students complained that the understanding of the mathematical material that consists of 12 modules covering subject matter of logic, reasoning and mathematical systems, linear equations and inequalities, quadratic equations and inequalities, sets, relations and functions, opportunities, social arithmetic, introduction to statistics 1, introductory statistics II, problem solving, transformation, congruence and similarity is very difficult understanding and presentation boring. Similarly, the results are not satisfactory. My observations as the Responsible Territory Madiun to tutor in delivering course material math module discusses a matter still is one-way. Tutor more material in a lecture delivered rarely interspersed with questions, the interaction between the tutor and the student so that the student is less passive. This research is to answer the question of how the effect of the application of the pillars of CTL in an effort to increase understanding of mathematical material. This research is a Class Action Research with steps that constitute a cycle or a cycle consisting of a plan of action, implement the action, observing, and reflecting. From the analysis of the data showed that a class action research by applying the pillars CTL is successful . .Keywords : improvement, understanding of mathematics, CTL and learning.